Emergence of Human West Nile Virus Infection in Sri Lanka - Lohitharajah, J.; Malavige, G.N.; Chua, A.J.S.; Ng, M.L.; Arambepola, C.; Chang, T. (BioMed Central, 2015)
Background: West Nile virus (WNV) has emerged as one of the most common causes of epidemic meningoencephalitis worldwide. Most human infections are asymptomatic. However, neuroinvasive disease characterized by meningitis, encephalitis and/or acute flaccid paralysis is associated with significant morbidity and mortality. Although outbreaks have been reported in Asia, human WNV infection has not been previously reported in Sri Lanka. Methods: Sera and cerebrospinal fluid (CSF) from 108 consecutive patients with a clinical diagnosis of encephalitis admitted to two tertiary care hospitals in Colombo, Sri Lanka were screened for WNV IgM antibody using enzyme-linked immunosorbent assay. Positive results were confirmed using plaque reduction neutralization test (PRNT). Patient data were obtained from medical records and by interviewing patients and care-givers. Results: Three of the 108 patients had WNV IgM antibody in serum and one had antibody in the CSF. The presence of WNV neutralizing antibodies was confirmed in two of the three patients using PRNT. Two patients had presented with the clinical syndrome of meningoencephalitis while one had presented with encephalitis. One patient had CSF lymphocytic pleocytosis, one had neutrophilic pleocytosis while CSF cell counts were normal in one. CSF protein showed marginal increase in two patients. Conclusions: This is the first report of human WNV infection identified in patients presenting with encephalitis or meningoencephalitis in Sri Lanka. There were no clinical, routine laboratory or radiological features that were distinguishable from other infectious causes of meningoencephalitis.
Keywords: West Nile virus; Encephalitis; Meningoencephalitis; Sri Lanka